Samuel Frederick and Valerie Heffernan, eds. Robert Walser: A Companion. Northwestern UP, 2018. - Domenic DeSocio (Studies in 20th & 21st Century Literature, 2021)
Review of Samuel Frederick and Valerie Heffernan, eds. Robert Walser: A Companion. Northwestern UP, 2018. ix + 298 pp.
Keywords: Robert Walser